Efficient Regulation of CO2 Assimilation Enables Greater Resilience to High Temperature and Drought in Maize - Correia, Pedro M. P.; da Silva, Anabela Bernardes; Vaz, Margarida; Carmo-Silva, Elizabete; Marques da Silva, Jorge (Frontiers in Plant Science, 2021)
Increasing temperatures and extended drought episodes are among the major constraints affecting food production. Maize has a relatively high temperature optimum for photosynthesis, however the response of this important C4 crop to the combination of heat and drought stress is poorly understood. Here, we hypothesised that resilience to high temperature combined with water deficit would require efficient regulation of maize photosynthetic traits, including the C4 CO2 concentrating mechanism. Two maize genotypes with contrasting levels of drought and heat tolerance, B73 and P0023, were acclimatized at high temperature (38 vs 25°C) under well-watered or water deficit conditions. Photosynthesis performance was evaluated by gas-exchange and chlorophyll a fluorescence, and in vitro activities of key enzymes for carboxylation (phosphoenolpyruvate carboxylase), decarboxylation (NADP-malic enzyme), and carbon fixation (Rubisco). Both genotypes successfully acclimatized to high temperature, although with different mechanisms: while B73 maintained photosynthetic rates by increasing stomatal conductance (gs), P0023 maintained gs and showed limited transpiration. When water deficit was experienced in combination with high temperatures, limited transpiration allowed water-savings and acted as a drought stress avoidance mechanism. Photosynthetic efficiency in P0023 was sustained by higher phosphorylated PEPC and electron transport rate near vascular tissues, supplying chemical energy for an effective CO2 concentrating mechanism. These results suggest that the key traits for drought and heat tolerance in maize are limited transpiration rate, allied with a synchronized regulation of carbon assimilation metabolism. These findings can be exploited in future breeding efforts aimed at improving maize resilience to climate change.